A Bibliometric Study on the Literature of Critical Pedagogy: Trends, Themes, and Future Directions - Ayhan Ural; Atilla Özdemir (Yaşadıkça Eğitim)
This bibliometric analysis examines the literature on critical pedagogy from 1986 to 2023, highlighting significant trends, influential authors, key institutions, and the evolving nature of the field. The study reveals a substantial increase in publications, particularly in recent years, reflecting growing interest and expanding research addressing contemporary issues such as social power relations, inequality, and democratic education. Influential figures like Peter McLaren and Henry A. Giroux have significantly shaped the theoretical and practical foundations of critical pedagogy. Key institutions, including the University of California and Victoria University, have played crucial roles in advancing research and fostering collaborations. Thematic analysis identifies democracy, cultural literacy, and identity politics as central themes, explored through various lenses like poststructuralism, gender, race, and sexuality. The findings underscore the interdisciplinary nature of critical pedagogy and its application across diverse educational settings. Based on these insights, recommendations for future research include fostering interdisciplinary collaboration, expanding studies to underrepresented regions, investigating emerging issues, strengthening the link between theory and practice, and conducting longitudinal studies to track the long-term impact. These steps aim to promote educational practices that are democratic, inclusive, and transformative.